1998
DOI: 10.1051/aas:1998416
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the local universe

Abstract: Abstract. This paper presents 2112 new 21-cm neutral hydrogen line measurements carried out with the meridian transit Nançay radiotelescope. Among these data we give also 213 new radial velocities which complement those listed in three previous papers of this series. These new measurements, together with the HI data collected in LEDA, put to 6 700 the number of galaxies with 21-cm line width, radial velocity, and apparent diameter in the so-called KLUN sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
188
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(220 citation statements)
references
References 5 publications
26
188
6
Order By: Relevance
“…Our new integrated flux value of 11.41 Jy·km s −1 is higher than past values measured at Arecibo or with single-pointing Nançay measurements (Bothun et al 1985;Lewis 1987;Haynes et al 1997;Theureau et al 1998), suggesting this galaxy has extended H i emission.…”
Section: Ugc 9024contrasting
confidence: 69%
See 2 more Smart Citations
“…Our new integrated flux value of 11.41 Jy·km s −1 is higher than past values measured at Arecibo or with single-pointing Nançay measurements (Bothun et al 1985;Lewis 1987;Haynes et al 1997;Theureau et al 1998), suggesting this galaxy has extended H i emission.…”
Section: Ugc 9024contrasting
confidence: 69%
“…An additional step was required for accurate flux calibration of our Nançay data, as it has been found that changes have occurred in the output power of the calibration diode used at Nançay since the early 1990's (see Figure 4 of Theureau et al 1998; see also Thuan et al 2000), resulting in an overall shift of the absolute cali-bration scale. This makes it necessary to appropriately renormalize the fluxes determined via the standard calibration techniques described above (e.g., Theureau et al 1998;Matthews et al 1998;Thuan et al 2000).…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This research has made use of the NASA/IPAC extragalactic database (NED), which is operated by the Jet Propul- Bottinelli et al (1990) and Theureau et al (1998) samples, the line width at 20% and 50% of the peak flux, W50 and W20, were provided, though not for all galaxies. In cases where only W20 was available, a conversion to W50 was made from a linear least-squares fit between these two quantities derived from those for galaxies for which both measurements were available.…”
Section: Discussionmentioning
confidence: 99%
“…According to Theureau et al (1998) A&A 545, L7 (2012) (Hamuy et al 2003) and 2005gj (Aldering et al 2006;Prieto et al 2007) are also plotted, assuming distance moduli of 37.32 mag and 37.09 mag respectively. Template optical light curves of SN 1991T (Nugent et al 2002) are plotted and scaled to match the absolute uBVri peak magnitudes of SN 1991T presented by Prieto et al (2007) and Saha et al (2001).…”
Section: Observationsmentioning
confidence: 99%